Comparison between siratro hay and mixed pasture of pangolagrass and centro for economical nursing of crossbred calves - Lima, Carlos Rodrigues; Souto, Sebastião Manhães; Lima, Therezinha de Almeida Oliveira (Pesquisa Agropecuaria Brasileira, 2014)
Sixteen crossbred (Holstein x Zebu) calves were used to compare methods of feeding. The calves were kept in individual pens and fed whole milk till 56 days of age. After days of age, eight of the calves were allowed free access to a pasture composed of pangolagrass and centro during the daytime. At three months of age, the calves were allowed acess to the pasture for 24 hours per day. The remaining eight calves were maintained in the pen receiving siratro hay "ad libitum". Average consumptions of milk and concentrate feed to 182 days of age were 161.7 kg and 382.5 kg, respectively. Analysis did not show significant differences (P < 0.05) between the treatments. However, there was a tendency for better gains with the hay and the feed costs were also lower for this treatment.